Sustainability and international trade in resources - Gernot Klepper; Frank Stähler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper discusses environmental policies which aim at a sustainable use of domestic resources which are mobile. It assumes that one country introduces such a policy but the other country does not. If a resource is mobile, strict domestic environmental policies may increase the resource imports from other countries. This paper shows that a unilateral environmental policy may even imply an increased resource use. In this case, a large part of the sustainability objective is met by substituting domestic resource extraction by imports. When sustainability is modelled in an inter temporal, competitive framework, the paper shows that the sustainability rule will not lead to a slower rate of extraction of the resource.
Keywords: F20; Q20; 330; international trade; factor mobility; sustainability; international environmental problems; Rohstoffmarkt; Faktormobilität; Außenwirtschaftstheorie; Umweltpolitik; Nachhaltige Entwicklung; Ressourcenökonomik; Theorie